Evaluation of two remediation techniques for the removal of silica from contaminated soil, Azandarian region, Iran - Arash Babaei; Maryam Bahrami; Masoomeh Maleki; Hadis Tavafi (سلامت و محیط, 2021)
Background and Objective: Bioremediation and one of its main branches, namely phytoremediation, is one of the most important and basic processes for eliminating pollutants from the environment. Due to the large number of silica factories in Azandarian area of ​​Malayer city and high soil silica pollution in this area, this study was conducted to compare the bioremediation effect of Fusarium oxysporum and Portulace olerace.L phytoremediation on silica uptake.